1995
DOI: 10.1017/s004317450008111x
|View full text |Cite
|
Sign up to set email alerts
|

Velvetleaf (Abutilon theophrasti) Recruitment, Survival, Seed Production, and Interference in Soybean (Glycine max)

Abstract: Field studies were conducted at Rosemount, MN, in 1992 and 1993 to quantify the demographic processes regulating the population dynamics of velvetleaf in soybean as part of a corn-soybean rotation. A consistent 6.8 ± 0.5% of the total velvetleaf seedbank emerged each year. Less than 21% of all velvetleaf seedlings survived each year in mixture with soybean, due in part toVerticilliumspp wilt infection. The probability of seedling survival varied across time of emergence. Velvetleaf seed production in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 33 publications
3
47
0
1
Order By: Relevance
“…One of the principal reasons for crop rotations has been to avoid the buildup of high inoculum loads of key plant pathogens. Lindquist et al (1995) and Hartzler (1996) have suggested that velvetleaf can be subjected to significant density-dependent dieback events caused by an unidentified Verticillium sp. Similarly, Fellows and Roeth (1992) showed that the recruitment of sorghum seeds from the seed bank was improved by treatment of seeds with fungicides when they were buried in the fall.…”
Section: Conservation Biocontrolmentioning
confidence: 99%
“…One of the principal reasons for crop rotations has been to avoid the buildup of high inoculum loads of key plant pathogens. Lindquist et al (1995) and Hartzler (1996) have suggested that velvetleaf can be subjected to significant density-dependent dieback events caused by an unidentified Verticillium sp. Similarly, Fellows and Roeth (1992) showed that the recruitment of sorghum seeds from the seed bank was improved by treatment of seeds with fungicides when they were buried in the fall.…”
Section: Conservation Biocontrolmentioning
confidence: 99%
“…This effect is magnified in the June cohorts, which had more difficult conditions to survive compared to more developed plants. Lindquist (1995) suggested a competition for light so that the late velvetleaf seedlings would be more affected due to a great canopy closure than to the present plant density. (Mulugeta and Stoltenberg 1997).…”
Section: Seedling Survivalmentioning
confidence: 99%
“…As was noted, for this species, by Lindquist et al (1995), the differences between cohort fecundity would be due to the fact that the earlier emerging plants will have an inherent advantage over later emerging individuals and therefore will be responsible for producing a greater number of seeds. These late emerged plants in a high density of other plants seem to present delayed reproduction and show a lower allocation to reproduction due to competition for light (Mabry and Wayne 1997).…”
Section: Seed Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Velvetleaf (Abutilon theophrusti Medik.) seed production was reduced up to 82% by competition with soybean (Lindquist et al, 1995). Increased shading, which often occurs when weeds emerge later than the crop, also reduces seed production.…”
Section: Additions To the Seed Batikmentioning
confidence: 99%